Regulatory peptides in the respiratory tract of Macaca fascicularis. Issue 6 (June 1987) - Ghatei, M A; Springall, D R; Richards, I M; Oostveen, J A; Griffin, R L; Cadieux, A; Polak, J M; Bloom, S R
Abstract : The quantitative distribution and localisation of seven regulatory peptides (vasoactive intestinal peptide (VIP), peptide histidine methionine (PHM), calcitonin gene related peptide (CGRP), galanin, substance P, neuropeptide tyrosine (Y), and bombesin like peptides) were determined by radioimmunoassay and immunocytochemistry in six different regions of the respiratory tract of the cynomolgus monkey, Macaca fascicularis. In general, peptide concentrations were higher in the airways than in lung tissue itself. VIP and PHM were found in greatest abundance and in equimolar concentrations. Concentrations of substance P, neuropeptide Y, and bombesin were substantially lower. Immunocytochemistry localised all the peptides to nerve fibres, whose density generally paralleled the tissue concentrations by radioimmunoassay except in the case of bombesin, which was not detected. VIP, PHM, and galanin were mostly associated with glands of trachea and bronchus and with blood vessels and smooth muscle; CGRP and substance P were found principally beneath airway epithelium and around smooth muscle fibres and blood vessels; neuropeptide Y was found around blood vessels and seromucous glands only. The pattern of peptide distribution in the Macaca fascicularis respiratory tract is similar to that previously reported in human postmortem material, suggesting that the cynomolgus monkey may be a useful model for examining the pathophysiological role of peptides in human respiratory disease.